2016
DOI: 10.26582/k.48.2.9
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of load and players’ effort in 4 vs 4 small-sided handball games in relation to court dimensions

Abstract: The aim of the present study was to analyse load to which players were exposed to and effort they invested in 4vs4 small-sided handball games in relation to various court dimensions. Eight male amateur handball players participated in three eight-minute 4vs4 (plus goalkeepers) small-sided handball games. The three court dimensions were 12×24 m, 30×15 m and 32×16 m. Using Global Positioning System devices (SPI pro elite 15hz, GPSports), time-motion video analysis, and Borg’s scale for rating of perceived exerti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(20 citation statements)
references
References 34 publications
1
17
1
1
Order By: Relevance
“…Also, HR max % results of all playing positions were almost equivalent regardless of aero-bic endurance, physical and body composition divergent of the players' positions conflicting with the previous study which measured lowest heart rate response in the goalkeepers [16]. Different from the findings presented here Corvino et al, showed that higher HR response by performing 4vs4 SSGs in different court sizes [6]. The observed increase in HR could be attributed to players have to be active in a vigorous place than their originally played space.…”
Section: Discussioncontrasting
confidence: 99%
See 4 more Smart Citations
“…Also, HR max % results of all playing positions were almost equivalent regardless of aero-bic endurance, physical and body composition divergent of the players' positions conflicting with the previous study which measured lowest heart rate response in the goalkeepers [16]. Different from the findings presented here Corvino et al, showed that higher HR response by performing 4vs4 SSGs in different court sizes [6]. The observed increase in HR could be attributed to players have to be active in a vigorous place than their originally played space.…”
Section: Discussioncontrasting
confidence: 99%
“…Previous studies have provided important information on the relation between SSGs and PlayerLoad in handball. It has been reported that different court sizes affect the PlayerLoad by increased distance covered in the larger playground during SSGs [5]. The study investigated that contact and non-contact SSGs, Iacono et al, have been demonstrated that both designed SSGs resulted in similar heart rate responses however non-contact SSG enables sprint and higher running pace than contact SSG [8].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations